BENEFITS AND LIMITATIONS OF USING SURGICAL GUIDES IN IMPLANTOLOGY - Kamel Earar; Mariana Jian; Norina Consuela Forna; Sergiu Focsaneanu; Alina-Ramona Dimofte; Nicolae Sârbu; Ovidiu Sebastian Nicolaiciuc (Romanian Journal of Oral Rehabilitation)
Surgical guides are an essential innovation in modern implantology, bringing significant benefits in terms of precision, predictability, and safety of procedures. Performed using advanced digital technologies, such as computed tomography (CBCT) and computer-aided design (CAD/CAM), they allow for accurate placement of implants, reducing the risks of deviation and complications. Benefits include reducing operative time, minimizing patient discomfort, and facilitating interdisciplinary collaboration, contributing to superior aesthetic and functional outcomes. However, the use of surgical guidelines also involves limitations. High costs, reliance on technology, anatomical constraints, and lack of intraoperative flexibility are challenges that can influence widespread adoption. In addition, their success depends on the clinician’s skills and the quality of the materials used, such as biocompatible resins and advanced polymers. Prospects include the integration of artificial intelligence for faster and more accurate planning, as well as the developing of sustainable materials and more affordable technologies. These advances will democratize the use of surgical guidelines and make implantology a safer and more effective practice. Surgical guides remain an essential tool in the modernization of implant treatments, providing substantial benefits for both patients and clinicians.